THE IMPACT OF REGIONAL GOVERNMENT EXPENDITURE AND INVESTMENT ON ECONOMIC GROWTH IN ACEH PROVINCE - Rahmatul Maula; Diana; Indra Wijaya (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to analyze the impact of regional expenditure and investment on economic growth in Aceh Province. The analysis employs a panel data regression method. The study population comprises all 23 regencies and cities in Aceh Province for the 2020–2024 period, with data obtained from Statistics Indonesia (BPS) and the Directorate General of Fiscal Balance (DJPPK). The results indicate that the Fixed Effect Model (FEM) is the most appropriate model, revealing that both regional expenditure and investment have a positive and significant effect on economic growth. This demonstrates that economic growth is driven not only by regional expenditure but also by the level of regional investment, highlighting the close interrelationship between these two variables in fostering economic growth in Aceh Province.